2005
DOI: 10.5713/ajas.2005.13
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of H-FABP Gene and Association with Intramuscular Fat Content in Laiwu Black and Four Western Pig Breeds

Abstract: This study was performed to detect genetic variation of the heart fatty acid-binding protein (H-FABP) gene by PCR-RFLPs approach and its association with intramuscular fat (IMF) content. Data from 223 individuals, including one Chinese native pig breed and four western pig breeds, were analyzed. The results showed that for the H-FABP gene, there was one polymorphic Hinf site Ⅰ in the 5'-upstream region, whereas there were one HaeIII and one HinfI (marked as HinfI*) polymorphic site in the second intron, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Emergence of MDR bacteria from poultry farms is a major threat to public health, especially in low-and middle-income countries. The poultry industry is among the rapidly growing agro-based enterprises with an annual increasing rate of 20% per annum in Bangladesh [35]. Being the major reservoirs of Campylobacter spp., poultry and livestock are mainly responsible for the ongoing spread of campylobacteriosis throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…Emergence of MDR bacteria from poultry farms is a major threat to public health, especially in low-and middle-income countries. The poultry industry is among the rapidly growing agro-based enterprises with an annual increasing rate of 20% per annum in Bangladesh [35]. Being the major reservoirs of Campylobacter spp., poultry and livestock are mainly responsible for the ongoing spread of campylobacteriosis throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…Laiwu Pig, an excellent type of North China local fatty breed of pig, is known for high meat quality with good tenderness (Zeng et al 2005 ), bright color, and higher IMF, while it is the best animal model to study the mechanisms of high intramuscular fat deposition (Spurlock and Gabler 2008 ; Chen et al 2013 ). The Lulai Black pig is a cross of a Laiwu pig with introgression of a Large White pig.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of symptomatic and asymptomatic infections in individual farms indicated that diverse combinations of multiple risk factors, concerning hygiene (e.g., hand washing, and proper cleaning), poultry rearing practices, waste disposal and health management, were synergistic socio-environmental drivers of the MDR Campylobacter pathogens in poultry sector.DiscussionEmergence of MDR bacteria from poultry farms is a major threat to public health, especially in lowand middle-income countries. The poultry industry is among the rapidly growing agro-based enterprises with an annual increasing rate of 20% per annum in Bangladesh[32]. Being the major reservoirs of Campylobacter spp., poultry and livestock are mainly responsible for the ongoing spread of campylobacteriosis throughout the world.…”
mentioning
confidence: 99%